2018
DOI: 10.1038/s41598-018-21547-y
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of photosynthesized carbon in an intensively farmed winter wheat–soil system as revealed by 14CO2 pulse labelling

Abstract: Understanding the rhizodeposited carbon (C) dynamics of winter wheat (Triticum aestivum L.), is crucial for soil fertility and C sequestration. Pot-grown winter wheat was pulse labelled with 14CO2 at the key growth stages. 14C in the shoots, roots and soil was measured at 5 or 2 days after 14C-labelling (DAL 5/2) at each growth stage and at harvest. The 14C in the shoots increased from 4% of the net 14C recovered (shoots + roots + soil) during tillering to 53% at harvest. Approximately 14–34% of the net 14C re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 45 publications
6
33
0
Order By: Relevance
“…The belowground transfer of ca. 20 % of assimilated C for all cultivars is in line with previous studies, which have reported fractions of similar magnitude for wheat plants, when not accounting for rhizosphere CO2 respiration: 18 -25 % (Hirte et al, 2018), 18 % (as reviewed by Kuzyakov and Domanski (2000)), 15 % (Keith et al, 1986), 17 % (Gregory and Atwell, 1991) and 31 % (Sun et al, 2018). In contrast, reported values of the partitioning of belowground translocated carbon by wheat plants to (i) roots and/or (ii) net rhizodeposition are much more variable.…”
Section: Carbon Allocation By Wheat Plantssupporting
confidence: 91%
See 2 more Smart Citations
“…The belowground transfer of ca. 20 % of assimilated C for all cultivars is in line with previous studies, which have reported fractions of similar magnitude for wheat plants, when not accounting for rhizosphere CO2 respiration: 18 -25 % (Hirte et al, 2018), 18 % (as reviewed by Kuzyakov and Domanski (2000)), 15 % (Keith et al, 1986), 17 % (Gregory and Atwell, 1991) and 31 % (Sun et al, 2018). In contrast, reported values of the partitioning of belowground translocated carbon by wheat plants to (i) roots and/or (ii) net rhizodeposition are much more variable.…”
Section: Carbon Allocation By Wheat Plantssupporting
confidence: 91%
“…In contrast, reported values of the partitioning of belowground translocated carbon by wheat plants to (i) roots and/or (ii) net rhizodeposition are much more variable. The same studies reported net rhizodeposition carbon as a percentage of total belowground carbon (root carbon and net rhizodeposition carbon combined) for wheat plants to be between 23 (as summarized by Kuzyakov and Domanski (2000)) and 72 % (Sun et al, 2018). The results obtained here (68 %) are thus at the high end of reported values.…”
Section: Carbon Allocation By Wheat Plantssupporting
confidence: 58%
See 1 more Smart Citation
“…The hydrothermal conditions of a wheat-soil system are essential to the dynamic balance of heat, moisture, and organic matter within the entire system and the thriving of wheat (Yang, Shang & Guan, 2012; Sun et al, 2018). Because of complicated biological, physical, and chemical processes like soil respiration, soil evaporation, plant transpiration, and so on, soil temperature and moisture have a close dynamic relationship with each other.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrothermal conditions of a wheat-soil system are essential to the dynamic balance of heat, moisture and organic matter within the entire system and the thriving of wheat (Yang et al 2012;Sun et al 2018). Because of complicated biological, physical and chemical processes like soil respiration, soil evaporation, plant transpiration and so on, soil temperature and moisture have a close dynamic relationship with each other.…”
Section: Introductionmentioning
confidence: 99%